Entamoeba histolytica Calreticulin Induces the Expression of Cytokines in Peripheral Blood Mononuclear Cells Isolated From Patients With Amebic Liver Abscess - Gonzalez Rivas, Enrique; Ximenez, Cecilia; Nieves-Ramirez, Miriam Enriqueta; Moran Silva, Patricia; Partida-Rodríguez, Oswaldo; Hernandez, Eric Hernandez; Rojas Velázquez, Liliana; Serrano Vázquez, Angelica; Magaña Nuñez, Ulises (Frontiers in Cellular and Infection Microbiology, 2018)
Calreticulin (CRT) is a highly conserved protein in the endoplasmic reticulum that plays important roles in the regulation of key cellular functions. Little is known about the participation of E. histolytica CRT (EhCRT) in the processes of pathogenicity or in the modulation of the host immune response. The aim of this study was to evaluate the role of CRT in the proliferation and the cytokine profile in peripheral blood mononuclear cells (PBMCs) from patients with amebic liver abscess (ALA) during the acute phase (AP-ALA) of the disease compared to patients during the resolution phase (R-ALA). The PBMCs from each participant were cocultured with EhCRT and tested by the colorimetric method to evaluate their proliferation index (PI). The supernatants were subjected to an enzyme-linked immunosorbent assay (ELISA) to evaluate the concentration of cytokines. The mean values of all groups were compared using the independent t-test. When the PIs of individuals without diagnosis of liver abscess (NEG) were compared, there were no statistically significant differences in the proliferation of PBMCs between patients with AP-ALA and R-ALA when stimulated with EhCRT or concanavalin A (ConA). However, the levels of interleukins [IL-6, IL-10, granulocyte colony stimulating factor (GCSF), and transforming growth factor β1 (TGFβ1)] were higher in patients with AP-ALA, whereas in patients with R-ALA, higher levels of interferon gamma (IFNγ) were detected. These results suggest that EhCRT acts as a mitogen very similar to the activity of ConA. In addition, EhCRT is an excellent immunogen for the specific activation of PBMCs, inducing the differential expression of ILs depending on the outcome of disease, determining the type of immune response: a Th2 cytokine profile during the acute phase and a Th1 profile during the resolution phase.